2017
DOI: 10.1039/c7ob00263g
|View full text |Cite
|
Sign up to set email alerts
|

Structure–functionality relationship and pharmacological profiles of Pseudomonas aeruginosa alkylquinolone quorum sensing modulators

Abstract: An important paradigm in anti-infective research is the antivirulence concept. Pathoblockers are compounds which disarm bacteria of their arsenal of virulence factors. PqsR is a transcriptional regulator controlling the production of such factors in Pseudomonas aeruginosa, most prominently pyocyanin. In this work, a series of tool compounds based on the structure of the natural ligand 2-heptyl-4-quinolone (HHQ) were used for probing the structure-functionality relationship. Four different profiles are identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
0
26
0
2
Order By: Relevance
“…[202] Aset of synthetic AIP-III analogues were found to be excellent inhibitors of all four AgrC receptors in both fluorescence reporter and hemolysis assays.T he most potent inhibitor,D 4A, exhibited picomolar IC 50 values. [193,[214][215][216] One key discovery was that an antagonist of the PQS and HHQ receptor PqsR, 6-nitro-HHQ,can undergo in vivo conversion to 6-nitro-PQS,w hich turns out to be ap otent PqsR modulator. [204] Besides employing AIP analogues to target AgrC,s ome active small molecules were discovered to interact with other gatekeepers of the Agr system.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…[202] Aset of synthetic AIP-III analogues were found to be excellent inhibitors of all four AgrC receptors in both fluorescence reporter and hemolysis assays.T he most potent inhibitor,D 4A, exhibited picomolar IC 50 values. [193,[214][215][216] One key discovery was that an antagonist of the PQS and HHQ receptor PqsR, 6-nitro-HHQ,can undergo in vivo conversion to 6-nitro-PQS,w hich turns out to be ap otent PqsR modulator. [204] Besides employing AIP analogues to target AgrC,s ome active small molecules were discovered to interact with other gatekeepers of the Agr system.…”
Section: Quorum Sensingmentioning
confidence: 99%
“…[210,211] Weitere Mçglichkeiten zur Manipulation dieses Stoffwechselweges ergaben sich durch die Fimbrolid-Naturstoffe,w elche phänotypische Veränderungen in verschiedenen Bakterienstämmen zur Folge hatten. [193,[214][215][216] Eine der Schlüsselentdeckungen war die Tatsache,d ass ein Antagonist des PQS/HHQ-Rezeptors PqsR, genannt 6-Nitro-HHQ,invivo eine Umwandlung zu 6-Nitro-PQs eingehen kann, was,wie sich herausgestellt hat, ein potenter PqsR-Modulator ist. [212,213] Zusätzlich zum Eingriff in diese drei klassischen QS-Pfade haben auch verschiedene Spezies-spezifische QS-Systeme wichtiger pathogener Bakterien die Aufmerksamkeit von Wissenschaftlern auf sich gezogen.…”
Section: Angewandte Chemieunclassified
“…Ausgiebige SAR-Studien brachten vielfältige synthetische PQS/HHQ-Agonisten oder Antagonisten hervor. [193,[214][215][216] Eine der Schlüsselentdeckungen war die Tatsache,d ass ein Antagonist des PQS/HHQ-Rezeptors PqsR, genannt 6-Nitro-HHQ,invivo eine Umwandlung zu 6-Nitro-PQs eingehen kann, was,wie sich herausgestellt hat, ein potenter PqsR-Modulator ist. Basierend auf diesen Ergebnissen wurde ein Carboxamid-Analogon synthetisiert, welches tatsächlich die Pyocyanin-Produktion inhibierte.D arüber hinaus schützte die Verbindung C. elegans in einem Nematoden-Assay vor einer Infektion mit P. aeruginosa PA 14 (Abbildung 15 d).…”
Section: Angewandte Chemieunclassified
“…These compounds were further improved regarding their efficacy in P. aeruginosa . We revealed that most potent QSI of this class act as inverse agonists rather than antagonists on the target receptor . In a similar approach, QSI containing a quinazolinone scaffold was discovered and helped resolving the crystal structure of the ligand binding domain of PqsR .…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] We revealed that most potent QSI of this class act as inverse agonists rather than antagonists on the target receptor. [24] In a similar approach, QSI containing a quinazolinone scaffold was discovered and helped resolving the crystal structure of the ligand binding domain of PqsR. [25] Furthermore, an HTS campaign led to benzamidebenzimidazole compounds showing efficacy in different mouse models, which emphasizes the in vivo relevance of targeting PqsR in infectious diseases.…”
Section: Introductionmentioning
confidence: 99%